2021
DOI: 10.1080/19338244.2021.1896986
|View full text |Cite
|
Sign up to set email alerts
|

Ambient hydrogen sulfide exposure increases the severity of influenza A virus infection in swine

Abstract: Hydrogen sulfide (H 2 S) is common in concentrated pig feed operations from the decomposition of manure. Ambient H 2 S is a respiratory tract irritant and an environmental stressor for caretakers and pigs. Influenza A virus (IAV), a zoonotic pathogen, has caused prior pandemics. The effects of H 2 S or IAV alone on the respiratory system have been investigated, but their interaction has not. We hypothesized that exposure to environmentally-relevant H 2 S concentrations increases the pathogenicity of IAV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In Figure 10D , it is of interest to see that ASVs assigned to the family Desulfovibrionaceae are found to act as kinless hubs. Although Desulfovibrionaceae was not found as a dominant family in our analysis at day 21, it is known to produce hydrogen sulfide ( H 2 S ), higher concentration of which is reported to increase the seriousness of IAV infection (Santana et al, 2021 ), while a reduced amount of H 2 S is found to protect against the viral infection (Dilek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…In Figure 10D , it is of interest to see that ASVs assigned to the family Desulfovibrionaceae are found to act as kinless hubs. Although Desulfovibrionaceae was not found as a dominant family in our analysis at day 21, it is known to produce hydrogen sulfide ( H 2 S ), higher concentration of which is reported to increase the seriousness of IAV infection (Santana et al, 2021 ), while a reduced amount of H 2 S is found to protect against the viral infection (Dilek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…We postulated that metabolic signatures of acute H2S poisoning were different from those following subchronic exposure to low level ambient H2S as clinical presentations are different [3,[5][6][7][8][9]12,13,20]. We therefore conducted this study to understand brain metabolomic changes induced by a single acute exposure to a high concentration of H2S and that caused by subchronic exposure to ambient concentration of H2S.…”
Section: Introductionmentioning
confidence: 99%